2012
DOI: 10.1177/1745790412445799
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pharmacists on drug purchasing behavior of price-sensitive consumers

Abstract: The present study empirically investigates how much pharmacists' recommendations and consumer decisions influence the marketing of drugs to price-sensitive consumers. The results indicate that consumers rely on physicians and their own decisions than pharmacists' recommendations in choosing prescription drugs. Consumers rely more on pharmacists' recommendations in purchasing over-the-counter drugs. To reveal the relationships among physicians, pharmacists, and consumers, pharmacists and consumers were surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…OTC’s price may play not only the decisive role in the consumers’ selection (Kohli and Buller, 2013), but has an important effect on attitude towards repeated purchasing (Lodorfos et al, 2006). Ricks and Mardanov (2012) found that price-sensitive consumers trust and follow the pharmacist’s recommendations in choosing low-cost alternative medicines.…”
Section: Discussionmentioning
confidence: 99%
“…OTC’s price may play not only the decisive role in the consumers’ selection (Kohli and Buller, 2013), but has an important effect on attitude towards repeated purchasing (Lodorfos et al, 2006). Ricks and Mardanov (2012) found that price-sensitive consumers trust and follow the pharmacist’s recommendations in choosing low-cost alternative medicines.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them had low knowledge about OTC drugs and there were barely any who carefully accessed OTC drugs and used prescription from doctors. The objective of the study conducted by (Ahmad et al, 2015) was very similar to above, plus, a comparison being made in the awareness in rural versus urban areas of India (Ricks and Mardanov, 2012). It was a cross-sectional study and data was pre-de ined from the studied population.…”
Section: Resultsmentioning
confidence: 99%
“…Medicines have always been a very important part of people's lives to protect and cure people from different diseases and injuries (Traulsen and Noerreslet, 2004;Ricks and Mardanov, 2012;Singh and Smith, 2005) . If not medicines, most of the diseases in this world would still have been incurable (Mathialagan and Kaur, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, despite the technological advancements and the availability of multiple points of reference in Western countries, the interpersonal influence exerted by pharmacists outperformed not only mass media channels, such as the Internet or the television (Table 2), but also other established sources of medical information, such as the doctor, rendering them the most vital part of people's word-of-mouth environment. 4 By contrast, a visit to the doctor represented the most likely patient reaction to the appearance of a symptom in the head and neck area (Table 5). This attitude confirmed the superiority of interpersonal as opposed to mass media sources of specific medical information in Western European societies, even after the tectonic shift which occurred in the ways in which patients obtain health and medical information in the past decade.…”
Section: Discussionmentioning
confidence: 99%